Soil microorganisms and their relationship with coffee beverage quality: A review - Rojas-Chacón, José Andrés (2024)
Introduction. Coffee (Coffea spp.) is the second most traded product globally and is cultivated in over eighty countries. Its cultivation is complex because it belongs to an ecosystem where abiotic and biotic factors interact under various agronomic management conditions. To understand the development of the coffee plant and its influence on the sensory quality of the final product, it is necessary to explore the intricate interactions between the coffee plant and the native microorganisms within the crop environment. Objective. To describe the role of the coffee soil microbiota, specially bacteria and fungi, and how they may contribute to the final quality of the beverage. Development. Soil is one of the most diverse and least studied ecosystems, where crucial ecological functions for plant growth and development take place. Identifying soil microbial components and their interactions with other organisms is important from an agronomic perspective. The soil microbiota can enhance plant physiology; thus, this review aims to connect how the sensory attributes of coffee beverage can be positively influenced by soil microbiota. Articles from ScienceDirect, Scopus, Web of Science, and Google Scholar from 2011 to 2023 were reviewed. The data show the diversity of plant growth-promoting rhizobacteria (PGPR), nitrogen-fixing bacteria (NFB), and arbuscular mycorrhizal fungi (AMF) associated with coffee cultivation. Additionally, microbial compounds play an important role in the formation of sensory attributes and are related to the coffee cup quality. Conclusion. The microbial diversity of soil and on the fruit can synthesize or degrade compounds that affect the sensory profile of the coffee beverage, which could have implications for sustainability and quality.